The OPTIMIZATION OF THE IMPROVEMENT OF STUDENTS’ MATHEMATICAL LEARNING OUTCOMES BY USING THE INSTRUCTIONAL SYSTEM DEVELOPMENT PROCEDURE LEARNING MODEL (PPSI) IN SMP IT BAITUL QURAN LANGSA - Priyanda R; Fadhelina N; Novi, R A (Jurnal Dimensi Matematika, 2020)
This Classroom Action Research was aims to improve students' mathematical learning completeness through the instructional system development procedures learning model (PPSI). The research was implemented in Baitul Quran Junior High School in Langsa during the even semester of 2019-2020 Academic Year. The population of this study was all students of grade 8th at Baitul Quran Junior High School which amount 7 (seven) students, where the whole students were included into the sample of research. The direct sampling technique was used in this study related to the small number of population (<10). The data were collected by using pre-test and post-test method for the main and documentation as complementary. The data analysis shows that only two students on the pre-test or initial test which obtained more than 70 (Minimum completeness criteria) or around 28.57%. The post-test shows that students' mathematical learning completeness after the implementation of PPSI were increase to 5 students who got a value of more than 70 (Minimum completeness criteria) or around 85.71%. So that from the analysis of pre-test and post-test data it can be concluded that the use of instructional system development procedure learning model (PPSI) in Baitul Quran Junior High School can improve the students’ mathematical skill.